Excitonic photoconductivity of heterostructures based on gallium and indium selenides - Katerynchuk, V.M.; Kovalyuk, Z.D.; Tkachuk, I.G. (Functional Materials, 2017)
Present spectra of photosensitivity of various types of heterojunctions based on layered crystals A³B⁶ made of the Van der Waals connection of pairs on heteromer as well as covalent. We also discuss the features of excitonic bands of the crystals. Examples of the first type, the heterojunction are pairs of n-InSe-p-InSe and p-GaSe-n-InSe and p-GaSe-n-In₄Se₃, n-SnS₂-p-InSe. As examples of heterojunction with a the covalent bond are the other systems: In₂O₃-InSe, In₂O₃-Ga₂O₃-GaSe, In₂O₃-Ga₂O₃-GaTe. These heterojunctions formed with participation of their oxides of different chemical nature. In the case when the oxide has leading properties, it plays a direct active role in the heterojunction formation. However, the formation of the heterojunction using high temperature heating of the substrates at air, naturally leads to uncontrolled growth of its own oxides on p-GaSe and p-GaTe which shows dielectric properties.